Rzayeva, Nuriyya - (:unkn) unknown (My University, 2026)
Nuriyya Asgar Rzayeva was born on May 22, 1971, in the city of Baku. From 1978 to 1988, she studied at Secondary School No. 20 in the Oktyabr district of Baku and graduated successfully. In the same year, she was admitted to the Foreign Languages Institute named after the 50th Anniversary of the USSR. In 1993, she graduated from the Azerbaijan State University of Languages with a degree in teaching English and French. She began her professional career in November 1993 as an English language teacher at Secondary School No. 28 in Baku. Since November 1997, she has been teaching English at the Department of Foreign Languages of Azerbaijan Technical University. In 2005, she was elected to the position of Senior Lecturer at the department. In 2010, she was awarded the academic degree of Doctor of Philosophy in Philology by the Higher Attestation Commission under the President of the Republic of Azerbaijan. In 2015, she was conferred the academic title of Associate Professor in the Department of Foreign Languages. Since that year, she has continued her academic and teaching activities as an Associate Professor of the department. In 2020, by Presidential Decree No. 2394 of the Republic of Azerbaijan, she was awarded the honorary title of “Honored Teacher.”